Comparative Study of Vibration Signal Processing on Pipe Leak Case. (November 2019) - Anderiansyah,; Miasa, I Made
Abstract: This article proposes a model for a real-time monitoring system capable of identifying the occurrence of single event leak in pressurized water pipelines. The model utilizes two accelerometers which are installed on upstream and downstream of the leak. Experiments are conducted on an inch PVC pipeline and the vibration signal results are displayed and recorded into laptop with installed software. The vibration signal derived from each accelerometer are assessed and analysed by Fast Fourier Transformation (FFT) and Cross-Power Spectral Density (CPSD). The results indicate that by using this method, leak can be identified while the sensor's positioning can be vital in leak detection.